1989
DOI: 10.3109/02688698909002828
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Barbiturates on Cerebral Metabolism in Patients with Borderline Cerebrovascular Reserve during Intraoperative Transient Carotid Occlusion

Abstract: Sixty patients with borderline or frank insufficiency of their cerebrovascular reserve undergoing carotid endarterectomy were given enough short acting barbiturates, during cross clamping of the internal carotid artery, to cause EEG burst suppression. Arterial and venous concentrations of lactate were measured in blood samples taken before, 30 min after occlusion of the artery and 10 min after reperfusion. The amount of lactate produced depended on the length of time of burst suppression; the shorter it lasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Review of the available literature documents the efflux of lactate with CEA or during cerebral injury as being potentially important to indicate brain-at-risk -but not the converse. 9,[17][18][19] Our findings are controversial, but new work strongly suggests that lactate may well be the preferred substrate for cerebral metabolism both anerobically and aerobically. [20][21][22][23] Thus, in the face of diminished oxygen supply, as with carotid cross-clamping in patients at risk, influx of lactate may be critically important to serve as a fuel for cerebral metabolism.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Review of the available literature documents the efflux of lactate with CEA or during cerebral injury as being potentially important to indicate brain-at-risk -but not the converse. 9,[17][18][19] Our findings are controversial, but new work strongly suggests that lactate may well be the preferred substrate for cerebral metabolism both anerobically and aerobically. [20][21][22][23] Thus, in the face of diminished oxygen supply, as with carotid cross-clamping in patients at risk, influx of lactate may be critically important to serve as a fuel for cerebral metabolism.…”
Section: Discussionmentioning
confidence: 81%
“…The monitors that are readily available include raw and processed electroencephalogram (EEG) analysis, 4 somatosensory evoked potentials (SSEPs), 5 Doppler flowmetry, 6 cerebral oximetry, 7 cerebral blood flow, 4,8 and assessment of measureable arterial to jugular venous differences (e.g., partial pressure of oxygen, carbon dioxide, glucose, lactate, and derived indices such as oxygen content). 9 Jugular venous blood sampling is a simple intervention during carotid endarterectomy, as the jugular vein is in the surgical field and direct retrograde cannulation is easily feasible. Recent work examining arterial-jugular venous sampling in patients undergoing awake CEA revealed that arterial-venous lactate difference was the most sensitive index of cerebral ischemia.…”
Section: Résumémentioning
confidence: 99%
“…Cerebral venous lactate levels are an accepted indicator of ischemic disturbance of cerebral metabolism. Wassman et al 13 have shown that longer intervals of burst-suppression (11 to 20 seconds) produce minimal change in cerebral arteriovenous difference lactate levels (arteriovenous difference lactate), compared with shorter intervals ( 1 to 5 seconds) where arteriovenous difference lactate is significantly higher, which suggests that longer . burst-suppression has a greater protective effect against ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…From our point of view, the application of neuroprotective measures, such as barbiturates, among others, should also be used to minimize the risk of brain metabolic disturbances. 2,3 The adoption of microtechniques (operating microscope and microequipment) for precise performance of endarterectomy contributes to a low complication rate, as experienced by our senior authors (S.P., H.W.) in more than three decades of carotid and cerebrovascular surgery.…”
Section: Editormentioning
confidence: 95%